USTA SPEAKS ISSUE 1 (2015)
The Foreign Language Institute (FLI) is pleased to present the first issue of our virtual bulletin: USTA Speaks. A virtual, academic environment to enable and encourage the USTA community to explore the writing competences in a foreign language. This is a great opportunity to promote multi-cultural awareness and expand the understanding of the rich diversity of learning foreign languages and make possible the break of world barriers. It is also a space to foster intellectual curiosity, critical thinking, and creative minds in our students.